(untitled) (Asian Journal of Medical and Biological Research, 2022)
Good hygiene and sanitation are essential for the prevention of infectious diseases. Immunization is one of the most important public health interventions to reduce both morbidity and mortality of infectious diseases. Thus, the survey study aimed to determine the status of hygienic practices and assess the immunization coverage among 12-59 months old children in urban slums. A cross-sectional study was conducted among 259 under five children’s (12-59 months) in Barisal city, Bangladesh, from June to December 2019 using a structured questionnaire. Data was collected by interviewing the mothers from different slum areas. Chi-squared test and multiple logistic regression models were used to explore the association. Prevalence of good hygiene practices status was 65.3% and fully immunized was 71.4%. Joint family (AOR=0.54; 95% CI: 0.31-0.95; P<0.05), monthly family income less than 10,000 BDT (AOR=0.52, 95%CI: 0.32-0.97; P<0.05) were less likely to practice good hygiene. Water along or ash/soil with water (AOR=5.32; 95%CI: 2.91-9.73; P<0.001), open toilet practices (AOR=81.1, 95%CI: 13.2-505.7; P<0.001) and suspended toilet facilities (AOR=2.77, 95%CI: 1.57-13.44; P<0.05) showed the likelihood to good hygiene practices. Illiterate mother (AOR=0.06; 95%CI: 0.09-0.79; P≤0.001), children living with joint family (AOR=0.08; 95%CI: 0.12-0.96; P≤.001) associated with lower immunization coverage. Immunization services center <10-minute walking distance from their living place (AOR =1.71; 95%CI: 1.02-2.87; P<0.05) associated with more immunization coverage status. The prevalence of hygiene practices status (65.3%) and immunization status (71.4%) in urban slums of Barishal city were reported less compared to the national level (86% immunization coverage). Some modifiable factors (water used within soap/soil, suspended toilet, the distance of immunization center, etc.) were significant with good hygiene practices and immunization coverage which are needed to improve for promoting good hygiene practices and reduce the infant mortality and morbidity rate. Asian J. Med. Biol. Res. 2022, 8 (4), 277-285